Endothelin‐1 receptor blockade as new possible therapeutic approach in multiple myeloma. (9th June 2017) - Russignan, Anna; Spina, Cecilia; Tamassia, Nicola; Cassaro, Adriana; Rigo, Antonella; Bagnato, Anna; Rosanò, Laura; Bonalumi, Angela; Gottardi, Michele; Zanatta, Lucia; Giacomazzi, Alice; Scupoli, Maria Teresa; et al.
Summary: New effective treatments are needed to improve outcomes for multiple myeloma (MM) patients. Receptors with restricted expression on plasma cells (PCs) represent attractive new therapeutic targets. The endothelin‐1 (EDN1) axis, consisting of EDN1 acting through EDN‐receptor A (EDNRA) and B (EDNRB), was previously shown to be overexpressed in several tumours, including MM. However, there is incomplete understanding of how EDN1 axis regulates MM growth and response to therapy. Besides EDNRA, the majority of MM cell lines and primary malignant PCs express high levels of EDNRB and release EDN1. Similarly, bone‐marrow microenvironment cells also secrete EDN1. Investigating the extent of epigenetic dysregulation of EDNRB gene in MM, we found that hypermethylation of EDNRB promoter and subsequent down‐regulation of EDNRB gene was observed in PCs or B lymphocytes from healthy donors compared to EDNRB‐expressing malignant PCs. Pharmacological blockade with the dual EDN1 receptor antagonist bosentan decreased cell viability and MAPK activation of U266 and RPMI‐8226 cells. Interestingly, the combination of bosentan and the proteasome inhibitor bortezomib, currently approved for MM treatment, resulted in synergistic cytotoxic effects. Overall, our data has uncovered EDN1‐mediated autocrine and paracrine mechanisms that regulate malignant PCs growth and drug response, and support EDN1 receptors as new therapeutic targets in MM.